Synthesis and structure-activity relationships of pyrimidine derivatives as potent and orally active FGFR3 inhibitors with both increased systemic exposure and enhanced in vitro potency. (1st March 2021) - Kuriwaki, Ikumi; Kameda, Minoru; Iikubo, Kazuhiko; Hisamichi, Hiroyuki; Kawamoto, Yuichiro; Kikuchi, Shigetoshi; Moritomo, Hiroyuki; Kondoh, Yutaka; Terasaka, Tadashi; Amano, Yasushi; Tateishi, Yukihiro; Echizen, Yuka; et al.
Graphical abstract: Abstract: Fibroblast growth factor receptor 3 (FGFR3) is an attractive therapeutic target for the treatment of patients with bladder cancer harboring genetic alterations in FGFR3. We identified pyrimidine derivative 20b, which induced tumor regression following oral administration to a bladder cancer xenograft mouse model. Compound 20b was discovered by optimizing lead compound 1, which we reported previously. Specifically, reducing the molecular size of the substituent at the 4-position and replacing the linker of the 5-position in the pyrimidine scaffold resulted in an increase in systemic exposure. Furthermore, introduction of two fluorine atoms into the 3, 5-dimethoxyphenyl ring enhanced FGFR3 inhibitory activity. Molecular dynamics (MD) simulation of 20b suggested that the fluorine atom interacts with the main chain NH moiety of Asp635 via a hydrogen bond.